The principle of the rule of law as the determiner of control of public administration implemented by the Prosecutor in administrative proceedings - Kozicka, Beata; Pierzchała, Ewa (The Opole Studies in Administration and Law, 2019)
Opus iustitiae PAX – the properly shaped dimension of justice is a guarantee of peaceful – not based on a conflict and violence – relations between citizens and the state. These words fully reflect the leading thought of this study. It is the concern for a good law and a state governed by the rule of law, which lies at the foundation of actions taken within the scope of legal means by the Prosecutor’s Office that – as the “custodian of law” – is entitled to in the sphere of control over administration. Administrative courts execute justice as a separate part of judicial power. Justice and law are conditions for an effective state, good governance and social peace, which have accompanied us for centuries. Administrative courts uphold the principle of equality before the law, which is regulated by Art. 21, par. 1 of the Constitution of the Republic of Poland. Since it is administrative courts which – by performing tasks of control over the activity of public administration – become the guarantee of realization of the above-mentioned principle, their position and range of cognition in the situation of launching administrative-court proceedings by the Prosecutor were presented in the work.